2017
DOI: 10.1002/jia2.25014
|View full text |Cite
|
Sign up to set email alerts
|

Brief counselling after home‐based HIV counselling and testing strongly increases linkage to care: a cluster‐randomized trial in Uganda

Abstract: IntroductionThe aim of this study was to determine whether counselling provided subsequent to HIV testing and referral for care increases linkage to care among HIV‐positive persons identified through home‐based HIV counselling and testing (HBHCT) in Masaka, Uganda.MethodsThe study was an open‐label cluster‐randomized trial. 28 rural communities were randomly allocated (1:1) to intervention (HBHCT, referral and counselling at one and two months) or control (HBHCT and referral only). HIV‐positive care‐naïve adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…As reported previously (Ruzagira, Grosskurth, Kamali, & Baisley, 2017 ) individuals in our trial who received follow-up counselling in addition to referral (intervention arm) after HBHCT were more likely to link to HIV care services than those who were referred only (control arm). Follow-up counselling may improve care seeking behaviour by providing specific information on how to access services (Ware et al., 2016 ), enhancing personal motivation (Knight, Van Rooyen, Humphries, Barnabas, & Celum, 2015 ), and reducing psychosocial barriers that inhibit linkage to care (Knight et al., 2015 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As reported previously (Ruzagira, Grosskurth, Kamali, & Baisley, 2017 ) individuals in our trial who received follow-up counselling in addition to referral (intervention arm) after HBHCT were more likely to link to HIV care services than those who were referred only (control arm). Follow-up counselling may improve care seeking behaviour by providing specific information on how to access services (Ware et al., 2016 ), enhancing personal motivation (Knight, Van Rooyen, Humphries, Barnabas, & Celum, 2015 ), and reducing psychosocial barriers that inhibit linkage to care (Knight et al., 2015 ).…”
Section: Discussionsupporting
confidence: 77%
“…The trial primary outcomes were linkage to care (clinic-verified registration for HIV care) determined six months after HIV diagnosis, and time to linkage. As reported previously, the trial intervention significantly increased linkage to HIV care and uptake of HIV care services (Ruzagira, Grosskurth, Kamali, & Baisley, 2017 ). This paper investigates factors associated with HBHCT uptake (i.e., the proportion who consented to an HIV test and received the result at home) among persons who were offered HBHCT.…”
Section: Methodssupporting
confidence: 64%
See 1 more Smart Citation
“…For those not already on ART, 73% were linked to care and initiated on ART within 12 months [ 16 ]. Other studies, like one in Uganda, have found only modest benefit from home visits to encourage ART initiation after home-based testing (34% intervention versus 26% control; HR = 1.31; 95% CI = 0.85–2.04) [ 17 ]. In South Africa, standard of care (SoC) mobile HIV counselling and testing units were compared with point-of-care (POC) CD4 alone, POC CD4 plus up to five care facilitation counselling sessions and POC CD4 plus transport reimbursement [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…registered with a facility providing treatment) within 1 month of their HIV counselling and testing (HCT) session [ 17 ]. Using home-based testing with augmented counselling in Uganda, another study achieved 44% linkage into care [ 18 ].…”
Section: Introductionmentioning
confidence: 99%